FOXA1 is a determinant of drug resistance in breast cancer cells - Kumar, Uttom; Ardasheva, Anastasia; Mahmud, Zimam; Coombes, R. Charles; Yagüe, Ernesto (Breast cancer research and treatment, 2021)
Purpose Breast cancer is one of the most commonly diagnosed cancers in women. Five subtypes of breast cancer differ in their genetic expression profiles and carry different prognostic values, with no treatments available for some types, such as triple-negative, due to the absence of genetic signatures that could otherwise be targeted by molecular therapies. Although endocrine treatments are largely successful for estrogen receptor (ER)-positive cancers, a significant proportion of patients with metastatic tumors fail to respond and acquire resistance to therapy. FOXA1 overexpression mediates endocrine therapy resistance in ER-positive breast cancer, although the regulation of chemotherapy response by FOXA1 has not been addressed previously. FOXA1, together with EP300 and RUNX1, regulates the expression of E-cadherin, and is expressed in luminal, but absent in triple-negative and basal-like breast cancers. We have previously determined that EP300 regulates drug resistance and tumor initiation capabilities in breast cancer cells. Methods Here we describe the generation of breast cancer cell models in which FOXA1 expression has been modulated either by expression of hairpins targeting FOXA1 mRNA or overexpression plasmids. Results Upon FOXA1 knockdown in luminal MCF-7 and T47D cells, we found an increase in doxorubicin and paclitaxel sensitivity as well as a decrease in anchorage independence. Conversely, upregulation of FOXA1 in basal-like MDA-MB-231 cells led to an increase in drug resistance and anchorage independence. Conclusion Together, these data suggest that FOXA1 plays a role in making tumors more aggressive.